Corporate Governance Disclosure and Corporate Governance Regulation: The Role of Investor Perceptions Towards Greenwashing - Lubis, Porkas Sojuangon; Batubara, Enika Diana; Lim , Chee Ann (International Journal of Sustainable Business, Management and Accounting, 2025)
Background of study: Increased global attention to sustainability has compelled companies to adopt Environmental, Social, and Governance (ESG) principles in their operations. However, the rise of greenwashing—misleading sustainability claims—has undermined investor trust and market transparency. Strong corporate governance and regulatory frameworks are expected to prevent such practices, yet challenges persist. Aims and scope of paper: This paper explores how corporate governance disclosure and environmental regulations shape investor perceptions of greenwashing. It also evaluates the effectiveness of existing regulations in preventing companies from engaging in deceptive ESG reporting. Methods: This study employs a qualitative approach through a comprehensive literature review, analyzing academic journals, regulatory reports, sustainability disclosures, and relevant case studies. The data were examined using content analysis to identify patterns and critical themes related to transparency, investor trust, and regulatory enforcement. Result: The findings indicate that although formal ESG regulations exist, gaps in enforcement, lack of independent audits, and inconsistency with international standards (e.g., GRI, SASB) still allow greenwashing to occur. Investor perception is significantly influenced by the clarity and credibility of ESG reports. Institutional investors and media play vital roles in pressuring companies toward transparency. Conclusion: Effective ESG regulation requires more than formal compliance; it demands robust enforcement, third-party audits, and alignment with global reporting standards. Investor engagement and stakeholder oversight are crucial in mitigating greenwashing risks. Strengthening transparency mechanisms will foster greater trust and support sustainable investment decisions.